Histopathological Spectrum of Splenectomy Specimens: A Six-Year Retrospective Study - Yamakanamardi, Basavaraj Dundappa; Shettar, Deepti Shivananad; Malashree; Myageri, Aneel (Annals of Pathology and Laboratory Medicine, 2025)
Background: The spleen plays a vital role in blood filtration and immune function but can be affected by a range of conditions requiring surgical removal. This study explores the histopathological findings in splenectomy specimens received at our institute and examines how these findings relate to clinical diagnosis. Methods: We conducted a retrospective study over six years (2016-2021) at the Department of Pathology, SDM College of Medical Sciences and Hospital, Karnataka. A total of 60 splenectomy specimens were analyzed through detailed gross and microscopic examination, with clinical data retrieved from medical records. Results: Of the 60 patients, 36 were male and 24 were female, with the most common age group being 31-40 years. The leading reason for splenectomy was blunt abdominal trauma (40%), followed by blood disorders like thalassemia intermedia (11.7%) and hypersplenism (8.3%). Histopathological examination most frequently revealed traumatic laceration (38.3%) and chronic venous congestion (36.7%), often linked to conditions like thalassemia and portal hypertension. Less common findings included splenic hamartomas, lymphangiomas, and Non-Hodgkin's lymphoma. Cystic lesions were identified in 10% of cases, including pseudocysts, mesothelial cysts, and epithelial cysts. Conclusion: Although splenectomy is not a routine procedure, its histopathological analysis provides valuable insights into underlying diseases. This study highlights trauma as the most common reason for spleen removal, followed by hematological and vascular disorders. Understanding these patterns can help improve diagnosis and patient management.